Clinical, endocrine and metabolic effects of metformin added to ethinyl estradiol-cyproterone acetate in non-obese women with polycystic ovarian syndrome: a randomized controlled study - (:unkn) unknown (OXFORD UNIV PRESS, 2002)
BACKGROUND: Oral contraceptive pills (OC) are usually the first choice of treatment for polycystic ovarian syndrome (PCOS), when fertility is not desired. However, they do not improve, or may even further induce impairment of insulin sensitivity, which is already impaired in women with PCOS. In this prospective, randomized study, we analysed the additional benefits of adding metformin to the OC treatment in non-obese women with PCOS. METHODS: After a baseline work-up including body mass index (BMI), waist:hip ratio (WHR), Ferriman-Gallwey score, ovarian volume, serum gonadotrophin, androgen and sex hormone-binding globulin (SHBG) levels, and fasting lipid, glucose and insulin levels, 40 non-obese women with PCOS were assigned either to the OC or to the OC + metformin treatment by computer-assisted randomization. At the end of the 4 month follow-up period, subjects were re-evaluated. RESULTS: The two groups were similar at baseline. After treatment, women in the OC + metformin group had significant decreases in BMI and WHR, and a significant increase in insulin sensitivity, in contrast to those in the OC group, who had insignificant changes in these parameters. Adding metformin also caused significant improvements in serum androstenedione and SHBG levels compared with the OC treatment alone. CONCLUSIONS: Adding metformin to the OC treatment may improve the insulin sensitivity, and may further suppress the hyperandrogenaemia in non-obese women with PCOS.
Keywords: cyproterone acetate; insulin resistance; metformin; oral contraceptive; polycystic ovarian syndrome; INSULIN-RESISTANCE; WEIGHT-LOSS; CARBOHYDRATE-METABOLISM; P450C17-ALPHA ACTIVITY; HYPERANDROGENIC WOMEN; GLUCOSE-TOLERANCE; SERUM ANDROGENS; RISK-FACTORS; SENSITIVITY; THERAPY